Deep Roots Supply Reactivity and Enhance Silicate Weathering in the Bedrock Vadose Zone - Ivan D. Osorio‐Leon; Daniella M. Rempe; Jon K. Golla; Julien Bouchez; Jennifer L. Druhan (AGU Advances)
Abstract In upland environments, roots commonly extend deep below soil into partially saturated bedrock. This Bedrock Vadose Zone (BVZ) has been shown to store and circulate water, host organic carbon respiration and serve as a critical source of rock‐derived nutrients. However, the extent to which deep roots influence chemical weathering rates remains poorly understood. Here, we report 4 years of depth‐resolved major ion chemistry over a 16‐m thick BVZ hosting a deep rhizosphere in a catchment subject to a Mediterranean climate. These data allow development and validation of a reactive transport model (RTM), revealing that the timescales of water storage and drainage in the BVZ are sufficient to facilitate substantial chemical weathering of the shale bedrock. However, observed solute concentrations are only reproduced by the RTM when we explicitly include measured rates of CO2(g) production meters below soil driven by the deeply rooted forest. By combining direct observations and a process‐based RTM we conclude that the carbon respiration promoted by deep roots significantly enhances chemical weathering rates in the BVZ, constituting 43% ± 3% of total solute flux from the base of the BVZ to the water table.